JUSTIFICATION OF RATIONAL PARAMETERS OF TRANSSHIPMENT POINTS FROM AUTOMOBILE CONVEYOR TO RAILWAY TRANSPORT - Khayitov Odiljon G’ofurovich; Umirzoqov Azamat Abdurashidovich; Ravshanov Zavqiddin Yaxyo ogli; Bekmuratov Ajiniyaz Omirbek ogli (Scholar Express Journals, 2021)
Justification of rational parameters of loading points from automobile and conveyor to railway transport is presented. Also, the paper will determine the main technological parameters of the rock mass transfer unit from the conveyor to the railway transport and justify the relationship between the parameters of the transshipment and transport complex of machines with the parameters of the rock mass dump in the scheme of cyclic-flow mining technology.
Keywords: Deposit, quarry, ore, mineral, conveyor, dump truck, railway transport, face, loading, ledge, volume, dumpcar, dumper